Band gap of reduced graphene oxide tuned by controlling functional groups. Issue 14 (12th March 2020) - Jin, Yiqian; Zheng, Yiteng; Podkolzin, Simon G.; Lee, Woo
Abstract : Functionalization of reduced graphene oxide with epoxide groups allows tuning its band gap energy. Abstract : Reduced graphene oxide (rGO) is a material with a unique set of electrical and physical properties. The potential of rGO for numerous semiconductor applications, however, has not been fully realized because the dependence of its band gap on the chemical structure and, specifically, on the presence of terminal functional groups has not been systematically studied and, as a result, there are no efficient methods for tuning the band gap. Here we report that the band gap of rGO can be increased and, importantly, tuned from 0.264 to 0.786 eV by controlling the surface concentration of epoxide groups using a developed mild oxidation treatment with nitric acid, HNO3 . Increasing the concentration of an HNO3 treatment solution gradually increases the surface concentration of epoxides without introducing microscopic defects or d -spacing changes and, thus, produces functionalized rGO materials with desirable properties for semiconductor applications. A combination of experimental measurements using infrared spectroscopy, ultraviolet-visible spectroscopy, X-ray diffraction, X-ray photoelectron spectroscopy, scanning electron microscopy and density functional theory calculations demonstrates that epoxides are unique among oxygen-containing functional groups for allowing to tune the band gap. Unlike epoxides, other oxygen-containing functional groups are not effective: hydroxyls do not change the band gap, while carbonyls and carboxyls break the hexagonal carbon-ring structure of rGO.